Pengaruh Komisaris Independen, Leverage, Profitabilitas, dan Risk Management Committee (RMC) terhadap Pengungkapan Enterprise Risk Management - Haryanti, Nurul Aulia; Hardiyanti, Widhian (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to examine the effect of independent commissioners, leverage, profitability, and risk management committee (RMC) on enterprise risk management (ERM) research in manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2020. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2020. This type of research is quantitative research that uses descriptive methods. The sampling technique used purposive sampling and obtained as many as 70 companies so that the total sample used in this study amounted to 280 samples. The data analysis method used is multiple linear regression analysis using the SPSS 25 application. Based on the results of the research conducted, it shows that independent commissioners, leverage, profitability, risk management committee (RMC) simultaneously have a significant effect on company risk management. While partially, independent commissioners have a significant negative effect on the use of corporate risk management. Leverage and profitability have no and no significant effect on the use of corporate risk management. The risk management committee has a positive effect on the company's risk management.